PENGARUH SISTEM INFORMASI AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL, DENGAN DESENTRALISASI SEBAGAI VARIABEL MODERAT : (Studi Kasus Pada Perusahaan Manufaktur di Kawasan Industri Pelabuhan Semarang) - Chairul Basyar; - Khanifah (Universitas Wahid Hasyim, 2008)
To be able to maintain the continuity of organizational life, needed by various important information is which is good for consideration in taking a decision. A lot of information, one of them is accounting information. The Relationship between accounting information with the performance managerial happened by decentralization, manager given the right to take the decision by supervisor and implementation, Based on background of above, hence this research take the problems that is how influence decentralize to information of system accounting management (broad scope, timeliness, aggregation, integration) with the performance managerial at manufacturing business in area of industry of port Semarang.Result of the research show that information which is consisted in characteristic of information system of accounting management and decentralization can be exploited by manager for the planning of, controlling, and making decision improved their ability comprehend the environmental situation in fact and identified relevant activities. There were authority delegation in decentralize system made manager needed information broad scope including (external and internal factors, non economic, non finance information, events in come period. The timeliness information made manager responded every problem and anticipated environmental uncertainty quickly so managerial performance can improved. Aggregation information made manager responded every problems in their responsibility unit. Integration information made manager evaluated managerial performance.Key words: Management Accounting Information System (Broadscope, timeliness, aggregation, integration), decentralization, managerial performance.